An Optical Method for a Bomb Scoring System - Curetti, María; García Bravo, Santiago; Arri, Gabriela Soledad; Clement, Beaudouin; Mathé, Ladislao (2022)
Fil: Curetti, María. Instituto Universitario Aeronáutico; Argentina.